Acute and sub-acute toxicity study of bacterial signaling inhibitor Solanum torvum root extract in Wister rats - Vadakkan, Kayeen (Clinical phytoscience, 2019)
Background Solanum torvum root extract is used to treat Asthma, Diabetes, and hypertension by Garo tribal healers of India and Bangladesh. Root tea is used to treat cough and fever by Attapadi tribal people of Kerala, India. The in vivo toxicological effects of Solanum torvum root extract was assessed by acute and sub-acute toxicity studies according to the OECD (Organisation for Economic Co-operation and Development) guidelines and per the guidance of Committee for the Purpose of Control and Supervision of Experiments on Animals (CPCSEA), Ministry of Environment and Forest, government of India. Results A single dose of Solanum torvum root extract (300 mg/kg, 600 mg/kg and 1200 mg/kg) was administrated daily for 14 days to estimate acute toxicity whereas subjects were treated for 28 days to assess the sub-acute toxicity. General functional behaviors, Physiological, histological, biochemical and hematological parameters were observed to understand the effect of extract upon study animal. All the study subjects were alive after the study period after acute and sub-acute toxicity assay. Functional and behavioral characteristics such as body position, respiration, clonic involuntary movement, tonic involuntary movement, palpebral closure, approach response, touch response, pinna reflex and tail pinch response; palpebral closure, lacrimation, salivation, piloerection, pupillary reflex, abdominal tone, limb tone, when held in hand were also found to be normal. Histological, biochemical and hematological parameters were also normal compared that with untreated group. Conclusions The acute and sub-acute toxicological analysis of Solanum torvum root extracts up on Wister rats suggested that there are no any dose response relation between extract administrated and toxicity, therefore there are no toxic effect by STRE, however more enlightenment regarding toxicity due to prolonged exposure can only be understood from chronic toxicity analysis.